Analisis Pendapatan Dan Strategi Pengembangan Usaha Budidaya Rumput Laut Di Desa Ungkea Kecamatan Petasia Timur Kabupaten Morowali Utara - Alber Tulak (Universitas Tadulako, 2017)
This research aims at identifying the income and the strategy of the development of seaweed farming in Ungkea Village Petasia Timur Sub-district Morowali Utara Regency. This research was applied through descriptive method and used qualitative approach. The setting of this research was determined purposively considering that Morowali Utara is one of area in Central Sulawesi Province that has seaweed farming. The sampples were taken through census method where the populations werw 44 respondents of seaweed farming. The data analysis used used is income and SWOT. The result of this research showed that the total cost avarage (TC) of seaweed farming in one period is consisting of permanent cost (FC) and variable cost (VC) is Rp 11.957.419,07 The total productions is 4.314 kg/432 expanses of 25m with selling price of Rp 9.000/kg then the farming obtained the avarage income of Rp 38.834.018 and net income about Rp 26.876.599,11. The cultivation of sea product of Eucheuma cattonii based on the calculation of R/C with ratio of 3.25>1, showed that this kind of business is worthy to be developed. The result of SWOT analysis revealed that this kind of business is in position of quadrant II that support the strategy of diversification with streagth-threats. The strategy of strength-threats (ST) maximizing the natural resources capacity in managing seaweed farming buseness and preventing various exist threats such as: climate change that caused pests and diseases in the seaweed. The involvement of the government through some programs pupports the management of fisheries sector as in business of seaweed farming that innovatively maximum and sustainable. Finally it improved the income and the welfare of the society in the coast of Morowali Utara Regency.